The BRICS and the G20. (July 2016) - Tian, Huifang
Abstract: Brazil, Russia, India, China and South Africa (BRICS) have come together economically as a group since 2009. Their cooperation has been driven not only by economic and political factors, but also the failure of the existing global economic governance framework to satisfy the real needs of these countries. In this paper, we analyze how the BRICS moved from a financial category into a political group, and are progressively developing from a dialogue‐based platform into a full‐fledged mechanism of long‐term coordination on a wide range of key issues relating to the world economy and politics. We also analyze how the BRICS have coordinated their positions in the G20, pushing for deep reform in global governance. Then, given the major hindrances to cooperation among the BRICS, including the challenge of economic transition, weak geopolitical links, complicated internal and external relations and inadequate governance capabilities, the present paper speculates on how the BRICS can use the opportunity arising from China taking the G20 presidency in 2016 to improve the cohesiveness and influence of the BRICS in terms of their agenda, organization and deliverables.